E-cigarette use and health information needs among a university student population in Melbourne, Australia - Kamoni, Tasneem; Selamoglu, Melis; Osadnik, Christian; Madawala, Sanduni; Kotwas, Susan; Turudia, Kim; Barton, Chris (Frontiers in Public Health, 2025)
ObjectiveWe explored e-cigarette use, e-cigarette knowledge, attitudes, intentions to use and access to e-cigarette health information among young adults enrolled at an Australian university.MethodsRespondents completed a survey about e-cigarette use and health resources about vaping. Data were analyzed using SPSS Version 28.0.ResultsResponses were received from n = 1,094 students aged 18–25 years. Current e-cigarette use was reported by 13.1% of respondents, daily use 7.6% and ever use 26.8%. Prevalence was greater among men, those reporting more psychological distress, alcohol use and worse academic performance. More than half (51.2%) perceived e-cigarette use as common among their peers and one-third were curious to try an e-cigarette in the future. Domestic and international student e-cigarette use was similar, however, international students tended to access less reputable sources for health information about vaping.ConclusionTailored strategies for domestic and international student groups are needed to address e-cigarette use among university cohorts. Universities provide a setting in which health information and cessation support can be provided to a well-defined group, by dedicated and well-resourced health and wellbeing teams. These results provide a rich resource to guide health promotion, prevention and cessation activities on campus.